Gender Analysis on the Effect of Tax Incentives, Tax Knowledge, and the Application of the E-Filing System on Tax Compliance (Survey of MSMEs in Bekasi City) - FATTAKH, Adam Navi’ul; TARMIDI, Deden (PT Keberlanjutan Strategis Indonesia, 2023)
The purpose of this research is to examine and analyze the differences and influence of tax incentives, tax knowledge, and the implementation of e-filing system on tax compliance from the point of view of male and female gender as an update from previous research. The population of this study is taxpayers who are MSME players in Bekasi city. The data collection method was carried out by distributing questionnaires to MSME taxpayers. The sample in this study used a simple random sampling method. The data processing technique uses Structural Equation Modeling (SEM) using SmartPLS 3.0. The results showed that 1) there is no difference in the effect of tax incentives on tax compliance from the point of view of male and female gender, this is because taxpayers who are male or female MSME players during the covid-19 pandemic have not received the benefits of tax incentives directly and have not fully participated in education related to information about tax incentives. 2) there are differences in the effect of tax knowledge on tax compliance, where male gender has a positive and significant effect while female gender has no effect. Male have more responsibility than female in working or running a business, especially during the covid-19 pandemic. MSME taxpayers with male gender in Bekasi city already have sufficient knowledge of tax law and administration in carrying out tax reporting.